2015
DOI: 10.1016/j.ijrobp.2015.07.339
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Transcriptomic Analysis Nominates Proteasomal Genes As Age Specific Biomarkers and Therapeutic Targets in Prostate Cancer

Abstract: BACKGROUND: Although prostate cancer (PCa) is hypothesized to differ in nature between younger versus older patients, the underlying molecular distinctions are poorly understood. We hypothesized that high-throughput transcriptomic analysis would elucidate biological differences in PCas arising in younger versus older men, and would nominate potential age-specific biomarkers and therapeutic targets. METHODS: The high-density Affymetrix GeneChip platform, encompassing 41 million genomic loci, was utilized to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…We found evidence of biologically more aggressive disease in men ≥80 years old than in men younger than 70 years, based on a) evidence consistent with previously reported associations of age and Gleason score,22 and b) novel results showing twofold and statistically significant increases in odds of positive p53 staining and higher MVD, after adjusting for race, screening status, PSA level, and Gleason score. The strength of association for bcl-2 staining was similar for men aged 80 years and older, but the result was not statistically significant in adjusted analyses.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We found evidence of biologically more aggressive disease in men ≥80 years old than in men younger than 70 years, based on a) evidence consistent with previously reported associations of age and Gleason score,22 and b) novel results showing twofold and statistically significant increases in odds of positive p53 staining and higher MVD, after adjusting for race, screening status, PSA level, and Gleason score. The strength of association for bcl-2 staining was similar for men aged 80 years and older, but the result was not statistically significant in adjusted analyses.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies have found dysregulated genes associated with DNA repair and androgen signaling in men over age 70 years,23 and also substantial differences in genes associated with progression to metastatic disease between older and younger groups 22. In addition, although published results are not entirely consistent, investigators are finding age differences for molecular markers in other tumor sites, including overexpression of TP53 in older (versus younger) individuals in meningioma, gastric cancer, and endometrial cancers 24–26.…”
Section: Discussionmentioning
confidence: 99%
“…However, no prognostic signature was tailored to predict aggressive CaP in men younger than age 55 years. Converging data from clinical and molecular genetic studies provide strong evidence that CaP in young men represents a distinct clinical phenotype with underlying biological differences compared to older men [9][10][11][12][13] . We hypothesized that age-related differences in tumor biology have implications for prognosis of early-onset CaPs.…”
Section: Introductionmentioning
confidence: 99%